Solutions for resource constrained IoT devices - Pereira, Felisberto Sequeira (2021)
Internet of Things (IoT) has been developing to become a free exchange of useful information between multiple devices. Already spread all over the world in the most varied forms and applications, IoT devices need to overcome a series of challenges to respond to the new requirements and demands. This thesis will focus on developing passive, semi-passive, and active solutions to overcome the energy and communication challenges faced by IoT devices. In that sense, several topics like backscatter communication, Wireless Power Transfer (WPT), Energy Harvesting (EH), chipless sensors, Simultaneous Wireless Information and Power Transfer (SWIPT), and Low-Power Wide- Area Network (LPWAN) will be explored and a set of contributions will be put forward. Moreover, whenever possible, the proposed solutions are implemented and tested in real application scenarios contributing to a better understanding of its viability.